Perencanaan Pembangkit Listrik Tenaga Surya Di Gedung A Kampus ITNY : Perencanaan Pembangkit Listrik Tenaga Surya Di Gedung A Kampus ITNY - nopriantoro, sulung; Diah Suwarti Widiastuti; Daru Sugati (Retii, 2024)
The utilization of New and Renewable Energy is being accelerated by the Indonesian Government. And one of the renewable energy resources that can be explored is solar energy. The potential for solar energy in Indonesia is very large, which is around 4.8 kWh/m2 or equivalent to 112,000 GWp, but only around 10 MWp has been utilized. The percentage of the value of Solar Power Plants that have been built in Indonesia is also only around 0.05% of the total power plants under the operation of PT. PLN (Persero). The ITNY campus has several tall buildings that have elongated roof contours and without shadow barriers from other buildings. Therefore, in this study, a Solar Power Plant plan will be made that will be installed on the roof of one of the buildings on the ITNY campus and operate On-Grid with electricity from PLN. The roof of the building used is Building A with an effective roof area that can be installed with a PLTS installation of 644 m2 divided into two sides, namely north and south. This On-Grid PLTS system will serve the electrical load of Building A of around 105,000 kW with loads in the form of lighting, power outlets and AC power. The result of this planning is a Roof-Top PLTS On-Grid system design that serves the electrical load for Building A. So it is hoped that with this PLTS system it is expected to reduce the monthly electricity bill of the ITNY Campus.